Pengaruh Terhadap Kepuasan Kerja Pegawai Di Dinas Perindustrian Dan Perdagangan Kabupaten Tapanuli Tengah - Rosmaita Ambarita; Leli Sudarma; Rizky Amelia; Aini Pandiangan; Seriana Veronica Siburian; T. Ahmad Helmi; M. Nelson Pinem (ARBITRASE: Journal of Economics and Accounting, 2023)
This research aims to find out the influence jointly or partially between competence, communication and organizational culture to the performance of the Workers at the Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Labuhanbatu. This research uses descriptive qualitative method using primary and secondary data. The population is the workers of the company. Forty workers become the sample of this research. Data analysis technique used is linear regression which shows that from the three independent variables applied to the regression model (competence, communication and organizational culture). Competence is significant for 0,000 which can be concluded that competence affects performance (hypothesis 1 accepted). Communication has significant value 0,011 which can be concluded that communication affects performance (hypothesis 2 accepted). Organizational culture variable has significant value 0,459 which means that organizational culture not influences performance (hypothesis 3 rejected). Research results show that competence, communication and organizational culture all positively influence the performance of the workers. It can be proven using the result of regression statistic test with probability value 0,000 obtained which is lower than ? (?=0,05). So, it can be said that competence, communication and organizational culture influence positively the performance of the workers. Thus, hypothesis 4 accepted.